2009
DOI: 10.1242/jcs.045401
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant function and structure of retinal ribbon synapses in the absence of complexin 3 and complexin 4

Abstract: Complexins regulate the speed and Ca2+ sensitivity of SNARE-mediated synaptic vesicle fusion at conventional synapses. Two of the vertebrate complexins, Cplx3 and Cplx4, are specifically localized to retinal ribbon synapses. To test whether Cplx3 and Cplx4 contribute to the highly efficient transmitter release at ribbon synapses, we studied retina function and structure in Cplx3 and Cplx4 single- and double-knockout mice. Electroretinographic recordings from single and double mutants revealed a cooperative per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 34 publications
12
81
0
Order By: Relevance
“…Molecular constituents of the photoreceptor ribbon synapses vary to some extent from those of conventional synapses and are likely best suited to fulfill these specific release requirements. They include the less prototypical SNAREs synaptobrevin-1 (Sherry et al, 2003) and syntaxin-3b (Morgans et al, 1996;Sherry et al, 2006;Curtis et al, 2008), and complexin-3 and -4 (Reim et al, 2009). Interestingly, the ERG phenotype reported in complexin-3/4 DKO mice (Reim et al, 2009) resembles the one observed in Munc13-2 KOs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Molecular constituents of the photoreceptor ribbon synapses vary to some extent from those of conventional synapses and are likely best suited to fulfill these specific release requirements. They include the less prototypical SNAREs synaptobrevin-1 (Sherry et al, 2003) and syntaxin-3b (Morgans et al, 1996;Sherry et al, 2006;Curtis et al, 2008), and complexin-3 and -4 (Reim et al, 2009). Interestingly, the ERG phenotype reported in complexin-3/4 DKO mice (Reim et al, 2009) resembles the one observed in Munc13-2 KOs.…”
Section: Discussionmentioning
confidence: 98%
“…Electroretinographic (ERG) recordings were performed on five pairs of age-matched (8-to 12-week-old) male wild-type or Munc13-2 KO mice that were dark-adapted overnight before commencement of the measurements. Both scotopic and photopic responses were recorded and analyzed as previously described (Reim et al, 2009). Shortly, mice were anesthetized by intraperitoneal injections of xylazine (50 mg/kg) and ketamine (20 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic analyses of interactions between Cpx and SNARE complexes by employing both glutathione S-transferase (GST)-pulldowns and a yeast four-hybrid interaction assay showed that Cpx binds efficiently to the SNARE complexes that are composed of either Syntaxin 1 or Syntaxin 3 [17][18][19][20] . Cpx does not bind efficiently to the SNARE complexes that are composed of either Syntaxin 2 or Syntaxin 4 [18,20] .…”
Section: Cpx Binds Efficiently To the Assembled Snare Complexes That mentioning
confidence: 99%
“…Four Cpx isoforms (Cpx1-4) are expressed mainly in the nervous system such as the brain, spinal cord, and retina, where neurotransmitters are released in a synchronous manner ( Figure 2A) [13,16] . In particular, membranebound Cpx3 and Cpx4 are expressed in retinal ribbon synapses where strong synchronous neurotransmitter release is required [17] .…”
Section: Snare Complexes That Are Involved In Mediating Synchronous Rmentioning
confidence: 99%